Är det omgivningen som får eleverna att ha svårt med matematik? - Öker,Ayberk (Master’s Theses in Mathematical Sciences, 2021)
Ayberk Öker (2020), Is it the environment that makes students have difficulty with mathematics?. Subject teacher education (mathematics and physics), Lund University. The purpose of the essay is to gain a deeper understanding of how the environment and social media affect children’s learning ability in mathematics. The impact of the conversations about mathematics and the posts in social media is taken up in the essay. I have conducted a survey and have used both qualitative and quantitative survey methods. Semistructured interviews with 25 high school students and 3 parents of different students as well as 8 structured interviews were conducted during my survey. To get a stronger conclusion, I have collected 61 questionnaires from one and the same school. During the interviews, I have collected information about the backgrounds of students and parents, their experiences, student’s thoughts and feelings about the mathematics, the home environment and the students´ environment. The conclusion that emerged is that the society which the student grows up has a great effect on the student’s learning ability and knowledge development. Everything that student hears and reads about mathematics shapes the student’s learning ability in a negative or positive way.
Keywords: Matematiksvårigheter; matematikängslan; miljöpåverkan; föräldrar; hemmiljö; math difficulties; math anxiety; environmental impact; parents; home environment.